Understanding perinatal vulnerabilities: how Aboriginal women’s cultural strengths and resilience shapes their social and emotional wellbeing - Ratajczak, Patricia; Reibel, Tracy; Munns, Ailsa; Walker, Roz; Marriott, Rhonda (Frontiers in Public Health, 2025)
BackgroundDuring pregnancy, childbirth and postnatally, women are at their most vulnerable, requiring health and social care systems able to meet their needs. In the context of perinatal care, assessing Aboriginal women’s mental health requires consideration of their whole-of-life to establish their overall social and emotional wellbeing. This requires mechanisms which respect women’s cultural positioning and needs. In the Australian health care system, Aboriginal women’s mental health is routinely viewed through mainstream screening and assessment tools, such as the Edinburgh Postnatal Depression Scale which does not address cultural strengths or the protective nature of being connected to culture. In the face of significant structural inequities, including in perinatal care, Aboriginal women are frequently marginalized which contributes to their disengagement from services. Despite this, women’s resilience remains evident and understanding why may hold the key to better perinatal care planning. As such, the aim of this study was to explore Aboriginal women’s resilience, self-efficacy and empowerment during their perinatal experiences, assessing factors contributing to their cultural strengths when addressing perinatal mental health concerns.Methodssituated in a larger pilot implementation project, this qualitative study used an Aboriginal Participatory Action Research method and was undertaken on Whadjuk Country, Boorloo (Perth Western Australia). Aboriginal women (n = 8) were invited to participate in yarns with the study’s lead Aboriginal researcher. Data was inductively and deductively analyzed, with findings interpreted through a decolonizing framework which prioritized strengths and cultural ways of being.ResultsSix themes were identified from analysis of the qualitative data: (1) strengthening identity-reconnecting to Culture; (2) connection to kinship/family sub-theme, strong partner support; (3) connection to country; (4) connection to culture; (5) resilience and self-efficacy; and (6) women’s experiences using the Baby Coming You Ready program’s digital platform. Themes 1–5 clearly demonstrated women’s strengths and resilience which were reported as a direct result of their culture and cultural connections; while theme 6 reported their positive experiences of using a strengths-based and culturally developed perinatal assessment platform.ConclusionThe results of this study confirm the positive benefits and value of co-designing tools for use in clinical settings which incorporate the cultural determinants of health and holistic perspectives of social and emotional wellbeing when screening Aboriginal women’s perinatal mental health.